Reconfiguring Governance and Control of State-Owned Enterprise Subsidiaries in Indonesia after the Establishment of Danantara - Tama Amelia Putri Sijabat; Baidhowi (Law Research Review Quarterly, 2026)
The establishment of the Daya Anagata Nusantara Investment Management Agency, hereinafter referred to as Danantara, through Law Number 1 of 2025 marks a fundamental shift in the governance and control of State-Owned Enterprises (SOEs), including their subsidiaries. This transformation replaces the previous governance model, which relied on the administrative authority of the Ministry of SOEs, with a centralized control framework implemented through investment management and holding mechanisms. This study aims to analyze the changes in governance and control over SOE subsidiaries following the establishment of Danantara, particularly with regard to the limits of state control authority, its implications for the principles of good corporate governance, and legal accountability within the SOE corporate group structure. The findings indicate that the establishment of Danantara strengthens state control over SOE subsidiaries both structurally and functionally, particularly through capital management, business planning, and the approval of strategic corporate actions, without altering the legal status of subsidiaries as independent limited liability companies. However, such reinforcement of control has the potential to restrict the autonomy of corporate organs and poses challenges to the implementation of the principles of independence and accountability. This study concludes that clear delineation of Danantara’s control authority is necessary to ensure consistency with the principle of entity separation and the implementation of good corporate governance.